2019
DOI: 10.3390/ijerph16234809
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Emotional Intelligence to Career Success: Beyond Personality Traits

Abstract: This study sought to investigate the role of emotional intelligence in both extrinsic and intrinsic career success in early and later career stages. Specifically, we examined the predictive and incremental validity of emotional intelligence in career success after controlling for personality factors in a sample of 271 graduates. When analyzing extrinsic career success, regression analyses revealed that demographic variables, such as gender, age, area of study and career stage, and the variable of proactive per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 85 publications
2
29
1
6
Order By: Relevance
“…This research aimed to determine the mediator role of burnout in the relationship between EI and performance. In prior studies [19][20][21][22][23][24][25][26], EI has been independently tested, and results demonstrated that EI predicts a better performance. However, the current work offers a new perspective in understanding the role of burnout in this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research aimed to determine the mediator role of burnout in the relationship between EI and performance. In prior studies [19][20][21][22][23][24][25][26], EI has been independently tested, and results demonstrated that EI predicts a better performance. However, the current work offers a new perspective in understanding the role of burnout in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that performance at work is strongly affected by emotions and feelings, which are an inherent part of the human existence in any context [18]. Those workers with higher emotional intelligence tend to be more successful [19,20], more productive [21,22], and less susceptible to perform counterproductive work behaviors [23]. Moreover, subjects with higher EI have shown more engagement than their colleagues [24], less burnout [25], and a lower intention to quit [26].…”
Section: Emotional Intelligence and Work Performancementioning
confidence: 99%
“…In the organizational context, different studies state that higher EI is related to higher scores in performance variables such as job satisfaction and team work effectiveness [ 6 , 7 , 8 ]. EI is also related to academic, professional, and career success [ 9 , 10 , 11 ]. Likewise, in the sports context, higher levels of EI are related to higher levels of physical activity [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, según Urquijo et al (2019), cuando se habla de políticas de responsabilidad social, se especula en la correspondencia que se promueve entre la empresa, el medio ambiente y el contexto social. Exiguamente se cavila en el recurso humano, y este aspecto se ha delegado en áreas como la gestión humana.…”
Section: Introductionunclassified